Sanitization system in Horticultural Sector - Luca Buglia (Advances in Horticultural Science, 2023)
The food industry has recognized the importance of environmental sanitation, and fruit control, a renowned leader in controlled atmosphere, has invested in sanitation through the use of ionizers to eliminate microorganisms in agri-food environments. This report presents results of tests conducted on various products, both in experimental and real scenarios in fruit and vegetable distribution platforms, to evaluate the effectiveness of ionization on vegetable products. The report covers three different situations: the first two focused on the effects of ionization on radish and table grape cells, while the last test verified the impact of ionization on a distribution platform that processes and markets various types of fruits and vegetables, such as pepper, tropical fruits, blueberry, apples, pears, table grape, chicory, and more.